Towards the development of antioxidant-wrapped graphene-based fluorescent nanomaterials having theranostic potentials: A combined experimental and theoretical study. (July 2021) - Karmakar, Abhijit; Mallick, Tamanna; Pramanik, Anup; Mandal, Debabrata; Begum, Naznin Ara
Abstract: We report here an easily implementable, economic and eco-friendly synthetic protocol for the antioxidant (DMAHF/DHF, 3-hydroxyflavone analogs)-wrapped fluorescent graphene oxide (GO). The antioxidant activity of DMAHF was further exploited to reduce GO; whereby DMAHF was oxidized. The mechanistic pathway of this rGO (reduced GO)-synthesis and its consequence on the fate of DMAHF; as well as the origin of spectral behavior of GO/rGO nanohybrid systems were understood by quantum chemical calculations and molecular docking studies. The GO/rGO-surface anchored (non-covalently) fluorescent antioxidant molecules (either in their native/oxidized forms) imposed characteristic fluorophoric nature to these nanohybrid systems. However, such interactions instigated a simultaneous quenching of the fluorescence of these molecules to some extent. Interestingly, the fluorescence of these nanohybrid systems was found to be largely enhanced in the presence of the biomolecules, like dsDNA (ctDNA). This was the basis of their activity as fluoroprobes for dsDNA. Being loaded with the bio-friendly antioxidant molecules, these nanohybrids can be potentially biocompatible. Thus, these graphene based nanohybrids with dsDNA-fluoroprobing efficacy and significant structural advantages can be promising candidates for the future development of advanced theranostic tools. Graphical abstract: Image, graphical abstract